2011
DOI: 10.1158/1055-9965.epi-10-1265
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in CYP1A1 and Ethnic-Specific Susceptibility to Acute Lymphoblastic Leukemia in Children

Abstract: Background: Acute lymphoblastic leukemia (ALL) is the most common childhood malignancy. The U.S. Surveillance Epidemiology and End Results (SEER) registry reports that Hispanic children have the highest incidence of ALL, however, it is unclear if this is due to genetic factors, unique environmental exposures, or both. Previous reports have shown an association between CYP1A1 variants and ALL.Methods: To explore the contribution of CYP1A1 polymorphisms to ALL susceptibility in different ethnic groups, we conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
2
30
0
1
Order By: Relevance
“…Two common polymorphisms in the CYP1A1 gene are a T6235C change within the 3' noncoding region of the gene (*2A, also known as the MspI restriction) and an A4889G change in the hems-binding domain of exon 7 (*2C). This polymorphism of the gene has been examined to cancer susceptibility [4,5,15].…”
Section: B Methods: Pcr-rflpmentioning
confidence: 99%
See 1 more Smart Citation
“…Two common polymorphisms in the CYP1A1 gene are a T6235C change within the 3' noncoding region of the gene (*2A, also known as the MspI restriction) and an A4889G change in the hems-binding domain of exon 7 (*2C). This polymorphism of the gene has been examined to cancer susceptibility [4,5,15].…”
Section: B Methods: Pcr-rflpmentioning
confidence: 99%
“…The involvement of this enzyme activity in the activation or de-activation shows the individual's susceptibility to cancer. The CYP1A1 polymorphism especially CYP1A1* 2A (T>C) will produce a cutting site for MspI enzyme; it has been linked to individual sensitivity to colon cancer [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…A second well-characterized variant in this gene, A4889G (rs1048943) evaluated by a fewer number of studies showed an elevated, but non-significant, risk estimate (homozygous: OR = 1.96, 95 % CI 0.92-4.19) in a metaanalysis of three studies [12]. A subsequent study conducted in a multi-ethnic US population of 258 B-lineage ALL cases and 646 matched controls reported a strong increased risk associated with A4889G observed predominantly in Hispanics (dominant: OR = 2.47, 95 % CI 1.13-5.38) [46]. Elevated risk estimates were reported in recent studies conducted in Brazil [47] and a multi-ethnic California population [16], but not in a Korean study [48].…”
Section: Xenobiotic Metabolism and Transportmentioning
confidence: 98%
“…These CYPs can generate reactive oxygen species directly by the inefficient coupling of NADPH consumption to substrate oxidation (Kopf and Walker, 2010; Morel et al, 1999; Schlezinger et al, 2006; Zangar et al, 2004) and indirectly by the metabolic activation of PAHs to highly reactive diol-epoxides and dihydrodiols (Bolton et al, 2000; Shimada, 2006). Furthermore, Hispanics commonly carry the CYP1A1*2A polymorphism (Swinney et al, 2011), which results in higher levels of CYP1A1 activity, and this increased CYP1A1 activity may put them at higher risk of cigarette smoke-induced oxidative stress. Thus, the degree to which the AHR is activated and the presence of the CYP1A1*2A polymorphism could be potential predictors of endothelial dysfunction in cigarette smokers.…”
Section: Introductionmentioning
confidence: 99%